2013
DOI: 10.1097/ppo.0b013e31829d74b4
|View full text |Cite
|
Sign up to set email alerts
|

A New Age for Vaccine Therapy in Renal Cell Carcinoma

Abstract: Over the past several years, the dominant paradigm in drug development for metastatic renal cell carcinoma (mRCC) has been to more selectively and potently target moieties such as the vascular endothelial growth factor receptor (VEGFR). The effectiveness of this strategy appears to be nearing a plateau, however, underscoring the need for novel approaches. Vaccine-based therapies represent one such approach. Several distinct vaccines are currently being examined in mRCC, each utilizing a distinct mechanism of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Vaccine strategies in cancer immunology can differ in the antigen used, the manufacturing mode, and the adjuvant used 85,86 . Attempts at treatment with modified virus vaccines targeting a single tumour antigen have been disappointing.…”
Section: Vaccinesmentioning
confidence: 99%
“…Vaccine strategies in cancer immunology can differ in the antigen used, the manufacturing mode, and the adjuvant used 85,86 . Attempts at treatment with modified virus vaccines targeting a single tumour antigen have been disappointing.…”
Section: Vaccinesmentioning
confidence: 99%
“…Phase I and II studies of the multipeptide mRCC vaccine IMA901 have demonstrated encouraging overall survival in the subset of patients who also received a single dose of cyclophosphamide in addition to the vaccine. [97][98] A randomized phase III study of IMA901, cyclophosphamide, and GM-CSF plus sunitinib versus sunitinib alone as fırst-line therapy for patients with metastatic RCC is currently ongoing. 99 AGS-003 is a personalized, autologous dendritic cell vaccine that has been examined in phase II clinical trials in combination with sunitinib.…”
Section: Mrcc Tumor Vaccinesmentioning
confidence: 99%
“…The field of genitourinary malignancies has been a showcase for therapeutic cancer vaccine success since the application of intravesicular Bacillus Calmette-Guerin (BCG) for bladder cancer in the 1970s [ 5 ] and enjoyed a renaissance in 2010 with the US Food and Drug Administration (FDA) approval of sipuleucel-T for prostate cancer [ 6 ]. Several vaccine strategies have emerged, such as autologous or allogeneic whole-tumor vaccines, DNA vaccines, use of viral vectors, and peptides as immunostimulatory adjuvants [ 7 , 8 ]. In addition to their elegant mechanism of action, vaccine strategies are clinically valuable for having a low adverse event profile.…”
Section: Introductionmentioning
confidence: 99%